Sosialisasi Bahaya Stunting dan Pemberian Abon Ikan Asap Sebagai Solusi Pemberian Makanan Tambahan (PMT) di Desa Randuputih - Puteri Arsalta Chandra; Ety Dwi Susanti (Yayasan Daarul Huda Kruengmane, 2023)
Stunting is a major health problem in Indonesia. In Randuputih Village there is one main problem in overcoming the high stunting rate, namely the problem of awareness. Counseling and applying the stunting hazard approach from an early age is one way to reduce the high existing stunting rate. Malnutrition can cause various problems, one of which is stunting. Even though stunting is a developmental disorder experienced by various children due to malnutrition, frequent infections and inadequate psychosocial stimulation. PMT intervention is one of the most important steps in reducing stunting rates in the regions.